IMPLEMENTASI PROGRAM KEAGAMAAN DALAM MEMBENTUK NILAI KARAKTER DISIPLIN PADA SISWA DI MI MIFTAHUL HUDA KABUPATEN MALANG - Muhammad Ainun Najib; Ika Ratih Sulistiani; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
This study aims to see how the implementation of religious program in makes the value of disciplinary characters in students in MI Miftahul Huda Kabupaten Malang. The problem is that many children today less have the attitude of discipline, so that teachers make religious activities in schools as the effert to make students with disciplined personalities. Data sources were obtained from school principals, PAI teachers, and islamic high school students. This study uses a qualitative method with the type of case study research, where the documents based on observations, interviews and documentation, analyzed with reduction documents, presentation documents, makes a conclusions and verifying conclusions. The results of this study indicate that the implementation of religious rograms is very important to make disciplined personalities by interacting between teachers and students and supervision of both parents. Kata kunci: Program Keagamaan, Karakter Disiplin.